Examining the "Culture of Assessment" in Public Libraries - Ferguson, Allison (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2022)
The introduction of the New Public Management (NPM) approach to public libraries globally brought with it a quality management paradigm typical of that used in for-profit corporations, characterized by an audit-intensive environment. This led to a desire for a “culture of assessment” to be the preferred standard within public libraries, largely in response to the threat of budget reductions and library closures. This review examines literature from the last two decades on the impact of this strategy, including themes such as the apparent consensus around library value (both in terms of qualitative facets and quantitative economic measures such as return on investment) and traditional and more recent approaches to measuring that value in both research and professional practice publications. Issues identified in the literature with the quantitative emphasis and threat narrative of the culture of assessment are discussed, as well as studies which examine the direct impact of NPM’s neoliberal ideology on public libraries.